Motherhood after cancer: fertility and utilisation of fertility-preservation methods - Goeckenjan, Maren (Arch Gynecol Obstet, 2020)
PURPOSE: Due to modern and individualised treatments, women at reproductive age have a high survival rate after cancer therapy. What are pregnancy and birth rates of women after cancer and how often do they use cryopreserved ovarian tissue or gametes? METHODS: From 2007 to 2015, 162 women aged 26.7 ± 6.9 years were counselled for fertility preservation at a single University Fertility Centre. A questionnaire study was performed in average 3 and 6 years after the diagnosis of cancer. The women were asked about their fertility, partnership, family planning, and pregnancy history. 72 women (51%) answered a written questionnaire in 2016. 59 women were reached again by phone in 2019 (82%). RESULTS: The preferred method of fertility preservation was ovarian tissue cryopreservation (n = 36, 50%); none of the women had ovarian hyperstimulation in order to cryopreserve oocytes. About 3 years after treatment, 37 women of 72 women (51%) of the women with a mean age of 29.9 years had a strong wish to conceive. 21/72 (29%) had actively tried to conceive after successful cancer treatment; eight women (11%) were already pregnant or had children. Six years after cancer diagnosis 16/59 (27%) women had ongoing anticancer treatment. 12/59 (20%) were pregnant or had children, while 39% (23/59) had no menstrual cycle. Only one woman used her cryopreserved ovarian tissue, but did not become pregnant. CONCLUSION: After cancer and gonadotoxic treatment, women’s desire to have a child is substantial. In this study, the rate of spontaneous pregnancies and births was 20% 6 years after gonadotoxic therapies. Not every woman, however, has the opportunity to conceive: factors impairing fertility include ongoing cancer treatment or persistent disease, no partner, no menstrual cycle, as well as other reasons for infertility.